EQUIPMENT AS MEDIA FOR PRACTISING IN THE FIELD OF THE GARMENT-RELATED TRAINING PROGRAMME OF VOCATIONAL TRAINING INSTITUTION IN LAOS - Santiphap Meunmany; Rita Fransina Maruanaya; Bounseng Khammounty (EDU SCIENCES JOURNAL, 2023)
Technical Vocational Education and Training (TVET) is understood as the component of education that results in the acquisition of applied and practical skills that will allow its trainees to find employment in a particular occupation. In order to effectively implement the program, these skills must be developed in a well-established and functional workshop with the appropriate tools, equipment, and machines for the ready-made garment training programme. The provision of workshop tools and equipment was a key of discussion in this study because it is essential for TVET graduates to develop the skills necessary for gainful employment in the ready-made garment industry. The purpose of this study was to focus on equipment alignment between VTI colleges and garment industries in Laos. This study used a descriptive qualitative research design. Literature review method and content analysis techniques were used to analyse the data, which focus on efforts to find, identify, and critically analyze the important elements in the document, namely: the equipment used in schools and in the garment industry. The result showed that the equipment as practical training equipment and tools in the vocational schools only covered the training objectives of the curriculum that the school has developed, in which students can only perform basic skills if compared to the equipment in the garment factory, it is only covered for 5% of equipment of the ready-made garment.